Jacob's gift - Lucado, Max.; Hunt, Robert, 1952- (Nashville : Tommy Nelson, 1998)
A young carpenter's apprentice works very hard on his woodworking project, only to give it away to a special baby.
3.8
K-3
K-3
Keywords: Jesus Christ -- Nativity -- Juvenile fiction; Jesus Christ -- Nativity -- Fiction; Jesus Christ -- Nativity -- Fiction; Carpenters -- Fiction; Carpenters -- Fiction